Effect of HLA-DRB1 alleles and genetic variants on the development of neutralizing antibodies to interferon beta in the BEYOND and BENEFIT trials. (April 2019) - Buck, Dorothea; Andlauer, Till FM; Igl, Wilmar; Wicklein, Eva-Maria; Mühlau, Mark; Weber, Frank; Köchert, Karl; Pohl, Christoph; Arnason, Barry; Comi, Giancarlo; Cook, Stuart; Filippi, Massimo; et al.
Background: Treatment of multiple sclerosis (MS) with interferon β can lead to the development of antibodies directed against interferon β that interfere with treatment efficacy. Several observational studies have proposed different HLA alleles and genetic variants associated with the development of antibodies against interferon β. Objective: To validate the proposed genetic markers and to identify new markers. Methods: Associations of genetic candidate markers with antibody presence and development were examined in a post hoc analysis in 941 patients treated with interferon β-1b in the Betaferon ® Efficacy Yielding Outcomes of a New Dose (BEYOND) and BEtaseron ® /BEtaferon ® in Newly Emerging multiple sclerosis For Initial Treatment (BENEFIT) prospective phase III trials. All patients were treated with interferon β-1b for at least 6 months. In addition, a genome-wide association study was conducted to identify new genetic variants. Results: We confirmed an increased risk for carriers of HLA-DRB1*04:01 (odds ratio (OR) = 3.3, p  = 6.9 × 10 −4 ) and HLA-DRB1*07:01 (OR = 1.8, p  = 3.5 × 10 −3 ) for developing neutralizing antibodies (NAbs). Several additional, previously proposed HLA alleles and genetic variants showed nominally significant associations. In the exploratory analysis, variants in the HLA region were associated with NAb development at genome-wide significance (OR = 2.6, p  = 2.30 × 10 −15 ). Conclusion: The contribution of HLA alleles and HLA -associated single-nucleotide polymorphisms (SNPs) to the development and titer of antibodies against interferon β was confirmed in the combined analysis of two multi-national, multi-center studies.